Enhanced flux pinning isotropy by tuned nanosized defect network in superconducting YBa2Cu3O6+x films - Mukarram Zaman Khan; Elmeri Rivasto; Jussi Tikkanen; Hannes Rijckaert; Mika Malmivirta; Maciej Oskar Liedke; Maik Butterling; Andreas Wagner; Hannu Huhtinen; Isabel Van Driessche; Petriina Paturi (NATURE PUBLISHING GROUP, 2025)
Striving to improve the critical current density Jc of superconductingYBa(2)Cu(3)O(6+x) (YBCO) thin films via enhanced vortex pinning, the interplay between film growth mechanisms and the formation of nanosized defects, both natural and artificial, is systematically studied in undoped and BaZrO3 (BZO)-doped YBCO thin films. The films were grown via pulsed laser deposition (PLD), varying the crystal grain size of the targets in addition to the dopant content. The microstructure of the PLD target has been observed to have a great impact on that of the deposited thin films, including the formation of vortex pinning centers, which has direct implications on the superconducting performance, especially on the isotropy of flux pinning properties. Based on experimentally measured angular dependencies of Jc, coupled with a molecular dynamics (MD) simulation of flux pinning in the YBCO films, we present a quantitative model of how the splay and fragmentation of BZO nanorods artifically introduced into the YBCO film matrix explain the majority of the observed critical current anisotropy.